EFEKTIFITAS STRATEGI READING A LOAD GURU DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QURAN SISWA - Cut Nya Dhin (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2019)
Ideally, the teacher can use a variety of appropriate strategies in the learning process. This study aims to find out how the level of students 'ability to read the Koran in MAN I Aceh Selatan and how teachers use learning strategies to improve students' ability to read the Koran in MAN I Aceh Selatan. Data collection techniques are carried out using observation, interviews, and documentation. This research is Field Research (field research) is descriptive qualitative analysis. The results showed that students of MAN I Aceh Selatan were able to read the Koran because of the cooperation between the principal and the teacher who was very selective in accepting prospective new students. Students' ability to read the Koran is different, for those who are not fluent. The solution made by teachers and principals is that they will be guided in extracurricular activities called the "tilawah" extracurricular activities conducted every Friday, which are taught how to pronounce the correct letters, speeches, tajweed and songs in reading the Koran. those who are already fluent and have good voices they will be appointed as peer teachers whose purpose is also to help students who are not fluent. In addition, the school will also bring teachers from LPIQ, so that children gain insight, are fluent and can be rhythmic, while the strategies used in Al-Quran learning children are required to "read a loud" when reading the Koran, they should not be ashamed, because their voices will be heard by friends and teachers, so that one another can judge each other and the teacher is easier to correct mistakes so they can be fast.